A facile synthesis of a solvent-dispersible magnetically recoverable Pd0 catalyst for the C–C coupling reaction. Issue 61 (10th June 2016) - Wu, Li; Yuan, Bin; Liu, Mengmeng; Huo, Hongfei; Long, Yu; Ma, Jiantai; Lu, Gongxuan
Abstract : A Pd 0 /Fe3 O4 -DA/DMG catalyst exhibited excellent catalytic activity toward the Suzuki, Heck and Kumada cross coupling reaction with a high yield. It is an especially efficient catalyst for Suzuki and Heck coupling in water. Abstract : Solvent-dispersible magnetite particles (Fe3 O4 ) functionalized with dopamine (DA) and N, N -dimethylglycine (DMG) were successfully prepared by a one-pot synthesis method with environment-friendly materials. Then Pd 0 nanoparticles were anchored onto the functionalized Fe3 O4 . The prepared materials were thoroughly characterized by TEM, XRD, XPS, FT-IR and VSM. The resultant magnetically recoverable Pd catalyst exhibited excellent catalytic activity for the C–C coupling reaction. In addition, this catalyst revealed high efficiency and stability during recycling stages. This work should be useful for the development and application of a magnetically recoverable Pd catalyst on the basis of green chemistry principles.